RECAPTURING „MARKETING‟ FROM THE „MARKETISATION‟ OF HIGHER EDUCATION DISCOURSE - Mateo, Adrian (European Scientific Journal, ESJ, 2015)
Both ‗marketing‘ and ‗marketisation‘ are features of the UK Higher Education (HE) sector. Whilst there is a close and often symbiotic relationship between marketisation and marketing, they represent distinctive aspects of the HE managerial discourse. Nevertheless, they have become part of an indivisible vocabulary that habitually misunderstands these distinctive concepts. The aim of this paper is to recapture marketing from the marketization discourse and demonstrate its contribution as a valid ideological perspective in HE.